Meet the press. July 18, 2010 - Cornyn, John, 1952-; Gregory, David, 1970-; Menendez, Robert, 1954-; Sessions, Pete, 1955-; Van Hollen, Chris, 1959- (New York, NY : NBCUniversal, 2010)
On this edition of Meet the Press: John Cornyn, Robert Menendez, Chris Van Hollen, and Pete Sessions discuss the future of the Republican Party and the president's performance.
Title from resource description page (viewed Aug. 14, 2014).
Broadcast Jul. 18, 2010.
In English.
Keywords: Obama, Barack; Filibusters (Political science); Fiscal policy; Political campaigns; Presidents -- America; Press conferences; Television news programs